Initial Validation of Mobile-Structural Health Monitoring Method Using Smartphones. (25th February 2015) - Yu, Yan; Han, Ruicong; Zhao, Xuefeng; Mao, Xingquan; Hu, Weitong; Jiao, Dong; Li, Mingchu; Ou, Jinping
Abstract : The structural health monitoring system has made great development nowadays, especially on bridge structures. Meanwhile, most SHM systems reported were designed, integrated, and installed into large-scale infrastructures by professionals and equipped with expensive sensors, data acquisition devices, data transfer systems, and so forth. And it is impossible to install SHM system for every civilian building. For this status, a kind of new idea for structural health monitoring using smartphone is introduced in this paper. A smartphone, with embedded responding SHM software and inner sensors or external sensors, can be used not only as a single wireless sensor node but also as a mini-SHM system. The method is described in detail, and then the swing test, cable force test in laboratory, and cable force test on an actual bridge based on the iPhone were conducted to validate the proposed method. The experimental results show that Mobile-SHM using smartphone is feasible. The realization of Mobile-SHM method using smartphones may be considered as a milestone in making SHM popular in the lives of people.